Customer Loyalty and Firm Performance: An In-depth Analysis of the Edible Oils Manufacturing Firms. - Mwazuna, Alice Ngele; Tibbs, Charles Yugi; Museve, Elijah; Asiimwe, Judith Bijurenda (Kabale University, 2024)
The study sought to analyze the effect of customer loyalty on the performance of edible oil manufacturing firms in Kenya. The constructs of customer loyalty included: repurchase, positive word of mouth, recommendations, and commitment to the brand while firm performance was measured using sales volume. The study adopted a causal research design and was underpinned by the customer loyalty business model. The target population was 535,840 which included 104 employees from the marketing departments of the three firms and 535,736 households from the middle-class estates in Nairobi the Yamane 1967 formula was used to get a sample size of 504 respondents and data was collected using a structured questionnaire and document analysis guide. Data was analyzed using descriptive statistics, linear regression, and correlation analysis and results were presented using tables. The findings revealed a positive and significant effect of customer loyalty on firm performance. The study concluded that all the aspects of Customer Loyalty as depicted by repurchase, positive word of mouth, recommendation, and commitment to the brand had a positive and significant effect on the performance of the edible oil manufacturing firms. The study, therefore, recommended that for firms to improve their performance and compete effectively in the market, they should strive to acquire and maintain loyal customers.